Therapeutic Crisis Intervention in Schools (TCI-S): An international exploration of a therapeutic framework to reduce critical incidents and improve teacher and student emotional competence in schools - Rodgers, Stella; Hassan, Sharinaz (Cambridge University Press (CUP), 2021)
Critical incident frameworks applied within schools are a means to support school staff to respond and guide planning to reduce critical incidents rates. This article explores the significance of the Therapeutic Crisis Intervention in Schools (TCI-S) critical incident framework to decrease the prevalence of behavioural critical incidents and to improve staff and student emotional competence in schools. The application of the TCI-S framework to reduce critical incidents within the United States and the United Kingdom school systems are demonstrated through upskilling school staff in social-emotional and co-regulation skills. It is suggested that TCI-S has the potential to support students with behavioural and emotional challenges and increase staff competency to implement trauma-informed practices that ultimately will reduce critical incidents.